FOREIGN EXPERIENCES ON RESTORATION OF DEGRADED LANDS AND INCREASING THE EFFICIENCY OF THEIR USE (Proceedings of International Educators Conference, 2023)
This article talks about foreign experiences in restoring degraded lands and increasing the efficiency of their use.